Pelatihan Media Pembelajaran Berbasis Augmented Reality bagi Guru SMKN 1 Binong - Ade Sukendar; Mellia Liyanthi; Fajar Darmawan (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
Learning media is an influential tool and plays a crucial role alongside teachers and students as the primary learning objects. These media often present material that is too abstract, making it difficult for students to understand. Therefore, learning media that can provide a detailed and concrete picture of the material are needed. The problem is that teachers are also required to be able to create learning media that can support creative and innovative learning processes, and make it easier for students to understand the material because the learning material is presented in a multi-sensory manner and provides a more realistic picture. It is also expected to help overcome learning problems faced by students, and to help optimize the use of information and communication technology as an effective and practical learning resource. This training helps improve teachers’ abilities in creating augmented reality (AR)-based learning media that previously did not know and understand. The devices used to run AR-based learning applications are 3D augmented reality object creation applications and smartphones.